Identifikasi Perilaku Adaptif pada Peserta Didik dengan Kesulitan Membaca: Studi Kasus dan Implikasinya - Yuliana, Syari; Nasri, Yosa Yulia; Rahma, Mulia Tia; Arnez, Gaby; Budi, Setia (Indo-MathEdu Intellectuals Journal, 2025)
The adaptive behavior of students struggling with reading is very important to discuss because it reveals a phenomenon that is often overlooked in the education world. At the age of grade 3 elementary school, children's reading ability is at a crucial stage, and the adaptive behaviors that arise from reading difficulties can provide important insights into their educational needs. The objective of this research is to observe and examine the adaptive behaviors of students experiencing reading difficulties in grade 3 at one of the schools in Padang City. This study uses a qualitative approach with descriptive methods. Data was obtained through observations, interviews, direct tests on students, and documentation. The data analysis technique employs qualitative data analysis through steps of data reduction, data presentation, and conclusion drawing. The analysis results show that this article demonstrates 5 adaptive behaviors of students facing reading difficulties in 3rd-grade elementary students. Teachers are strongly advised to develop teaching approaches that cater to the individual needs of students in relation to the 5 adaptive behaviors of students with reading difficulties.